2015
DOI: 10.1016/j.bbmt.2014.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Incidence Rate of Fluoroquinolone-Resistant Gram-Negative Rod Bacteremia among Allogeneic Hematopoietic Cell Transplantation Patients during an Era of Levofloxacin Prophylaxis

Abstract: Background There are concerns that emerging resistance to fluoroquinolones (FQ) may be leading to increasing rates of gram-negative rod (GNR) bacteremia in hematopoietic cell transplant (HCT) recipients. We set out to describe time trends in the incidence rates (IR) of GNR bacteremia and FQ-resistant GNR bacteremia in HCT recipients during an era of levofloxacin prophylaxis. Methods We conducted a longitudinal retrospective study of adults undergoing allogeneic HCT between 2003 and 2012 at the Seattle Cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 29 publications
0
19
0
2
Order By: Relevance
“…The design of the ONKO-KISS surveillance did not permit a more detailed analysis of the association of the trends of Gram-negative BSI and risk factors. Other studies, however, have reported an association between increased BSI due to Gram-negative bacteria and the emergence of fluoroquinolone resistance in E. coli [10,12,16], while others have reported inconsistent effects [24]. Furthermore, an increase of broad-spectrum b-lactamases has been reported in Gram-negative pathogens from many cancer centres [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…The design of the ONKO-KISS surveillance did not permit a more detailed analysis of the association of the trends of Gram-negative BSI and risk factors. Other studies, however, have reported an association between increased BSI due to Gram-negative bacteria and the emergence of fluoroquinolone resistance in E. coli [10,12,16], while others have reported inconsistent effects [24]. Furthermore, an increase of broad-spectrum b-lactamases has been reported in Gram-negative pathogens from many cancer centres [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, fluoroquinolone resistance in E. coli has increased significantly during recent years in oncology settings. These findings are of concern given that fluoroquinolone-resistant E. coli infections are associated with increased mortality in oncology patients [23]. Indeed, the impact of growing antimicrobial resistance in oncology has been highlighted recently [24].…”
Section: Discussionmentioning
confidence: 99%
“…After transplant, all patients received immunosuppressive agents as prophylaxis against graft-versushost disease in the post-transplant period. Standard infectious prophylaxis included acyclovir for herpes simplex virus and or varicella zoster virus; trimethoprim-sulfamethoxazole, atavoquone, or dapsone for Pneumocystis jirovecii; and fungal prophylaxis with fluconazole [9]. All patients received either ceftazidime or levofloxacin for neutropenic prophylaxis [10].…”
Section: Transplant Proceduresmentioning
confidence: 99%